Influence of Ramadan fasting on anaerobic performance and recovery following short time high intensity exercise - Karli, U.; Guvenc, A.; Aslan, A.; Hazir, T.; Acikada, C. (Journal of Sports Science & Medicine, 2007)
The aim of this study was to investigate the effects of Ramadan fasting on anaerobic power and capacity and the removal rate of lactate after short time high intensity exercise in power athletes. Ten male elite power athletes (2 wrestlers, 7 sprinters and 1 thrower, aged 20-24 yr, mean age 22.30 ± 1.25 yr) participated in this study. The subjects were tested three times [3 days before the beginning of Ramadan (Pre-RF), the last 3 days of Ramadan (End-RF) and the last 3 days of the 4th week after the end of Ramadan (After-RF)]. Anaerobic power and capacity were measured by using the Wingate Anaerobic Test (WAnT) at Pre-RF, End-RF and After- RF. Capillary blood samples for lactate analyses and heart rate recordings were taken at rest, immediately after WAnT and throughout the recovery period. Repeated measures of ANOVA indicated that there were no significant changes in body weight, body mass index, fat free mass, percentage of body fat, daily sleeping time and daily caloric intake associated with Ramadan fasting. No significant changes were found in total body water either, but urinary density measured at End-RF was significantly higher than After-RF. Similarity among peak HR and peak LA values at Pre-RF, End- RF and After-RF demonstrated that cardiovascular and metabolic stress caused by WAnT was not affected by Ramadan fasting. In addition, no influence of Ramadan fasting on anaerobic power and capacity and removal rate of LA from blood following high intensity exercise was observed. The results of this study revealed that if strength-power training is performed regularly and daily food intake, body fluid balance and daily sleeping time are maintained as before Ramadan, Ramadan fasting will not have adverse effects on body composition, anaerobic power and capacity, and LA metabolism during and after high intensity exercise in power athletes.